Selection of a Sustainable Strategy Using DSS for Students in Selecting the Faculty of Economics and Business with the Topsis Method - Mardjono, Enny Susilowati; Hariyadi, Guruh Taufan; Ratnawati, Juli (Jurnal Penelitian Ekonomi dan Bisnis, 2023)
Universities must be able to predict opportunities and challenges with the right interest in the students choosing majors in higher education in the digitalization era. This study provides the right strategy for FEB UDINUS by proposing a structural hierarchical model to analyze changes in student decision-making patterns in choosing the Faculty of Economics and Business at Dian Nuswantoro University in the digital market era by taking the context of sustainable value. The data collection techniques used in-depth interviews to determine student’s decision-making criteria in choosing FEB majors. The analysis of decision making factors was processed using TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). The results of this study show the ranking strategy of the most appropriate ranking such as the strategy to find credible partner, the strategy to provide additional community benefits, the strategy to educate the community, the strategy for building collaboration between students, the strategy for creating iconic brands, the strategy for building collaboration between faculty and students, the strategy for building new learning models, and the strategy for building a new learning culture. Keywords:Sustainable strategy, DSS, Topsis Method